Strategies of Business Capital, Manpower, and Innovation to Increase Turnover at Surya Mart Through Strengthening Muhammadiyah Leadership - Supardi Supardi; Sriyono Sriyono; Mohammad Rizal Yulianto (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
The swift competition within the Surya Mart business, which operates in the retail sector of household products, serves as the focal point of this study. The objective of this research is to ascertain the influence of Muhammadiyah’s business capital, manpower force, innovation, and leadership on its turnovers. This study seeks to assess the enhancement of Surya Mart’s turnover through the following approaches: (1) Examining the impact of the capital variable on the increase in Surya Mart’s turnover. (2) Investigating the influence of manpower on the augmentation of earnings and turnover. (3) Analyze the impact of innovation on the augmentation of turnover. (4) Assess the moderation effect of Muhammadiyah leadership on the relationship between business capital and turnover increase. (5) Evaluate the moderation effect of Muhammadiyah leadership on the relationship between manpower and turnover increase. (6) Examine Muhammadiyah leadership as a moderator of the impact of innovation on turnover increase. This research employs a quantitative approach, utilizing data collection methods including interviews, observations, and documentation. The research employs an incidental sampling technique, wherein the researcher selects population members who are deemed capable of furnishing information to bolster the research objectives. The data were analyzed using Smart-PLS. The analysis results indicate that business capital exerts an influence on turnover, manpower demonstrates a significant impact on turnover, and innovation contributes to affecting turnover. Muhammadiyah leadership does not moderate the impact of business capital on turnover. Similarly, Muhammadiyah leadership does not moderate the influence of manpower on turnover, nor does it moderate the effect of innovation on turnover.